1995
DOI: 10.1063/1.469091
|View full text |Cite
|
Sign up to set email alerts
|

Study of the low-lying states of Ge2 and Ge−2 using negative ion zero electron kinetic energy spectroscopy

Abstract: Electronenergyloss spectroscopy of condensed butadiene and cyclopentadiene: Vibrationally resolved excitation of the lowlying triplet states J. Chem. Phys. 98, 8397 (1993); 10.1063/1.464498Study of the lowlying electronic states of Si2 and Si− 2 using negative ion photodetachment techniques A study of the lowlying electronic states of Fe2 and Co2 by negative ion photoelectron spectroscopyThe low-lying states of Ge 2 and Ge 2Ϫ are probed using negative ion zero electron kinetic energy ͑ZEKE͒ spectroscopy. The Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…Formal oxidation states can be inferred by considering the electronic structures of Ge 2 – and TiGe 2 – . Although there are still arguments over the electronic ground state of Ge 2 – , the two lowest-lying states are theoretically and experimentally established as nearly degenerate. Both states 2 Π u [...2σ g 2 2π u 3 ] and 2 Σ g + [...2σ g 1 2π u 4 ] have one singly occupied orbital and can combine with titanium atoms to form TiGe 2 – . By comparing the leading orbital configurations of two lowest nearly degenerate states 4 B 1 and 2 A 1 of the triatomic species with that of Ge 2 – , one can recognize that the singly occupied orbital (π u and/or σ g ) of the Ge 2 – moiety becomes doubly occupied in TiGe 2 – , which means that one electron is actually transferred from titanium to the Ge 2 moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Formal oxidation states can be inferred by considering the electronic structures of Ge 2 – and TiGe 2 – . Although there are still arguments over the electronic ground state of Ge 2 – , the two lowest-lying states are theoretically and experimentally established as nearly degenerate. Both states 2 Π u [...2σ g 2 2π u 3 ] and 2 Σ g + [...2σ g 1 2π u 4 ] have one singly occupied orbital and can combine with titanium atoms to form TiGe 2 – . By comparing the leading orbital configurations of two lowest nearly degenerate states 4 B 1 and 2 A 1 of the triatomic species with that of Ge 2 – , one can recognize that the singly occupied orbital (π u and/or σ g ) of the Ge 2 – moiety becomes doubly occupied in TiGe 2 – , which means that one electron is actually transferred from titanium to the Ge 2 moiety.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic reference state for the diamagnetic complex is the 1 D g excited state (Figure 3 b), which is only 9.5 kcal mol À1 higher in energy. [26] The orbital occupation of the latter state is perfectly suited for donor-acceptor interactions with two NHC ligands. Figure 3 c shows that the vacant p-bonding orbital of the 1 D g state of Ge 2 can serve as an acceptor orbital for donation from the minus combination of the carbon lonepair orbitals of the NHC ligands (b u symmetry in C 2h ), while the associated p* antibonding MO (Figure 3 d) is available as an acceptor orbital for electron donation from the plus combination of the NHC donor orbitals (a g symmetry).…”
mentioning
confidence: 99%
“…0.04 2.33 313 [8] 0.06 2.38 195 [10] 0.08 2.32 278 [7] 0.10 2.34 251 [11] 0.08 2.37 297 Exp. [5] 0.11 *** 308 Exp. [1] 0.09 *** 308 Theoretical studies on singlet and triplet states of Ge 2 3259 Figure 7.…”
Section: Discussionmentioning
confidence: 98%
“…Negative ion zero electron kinetic energy (ZEKE) experiments on the Ge À 2 ! Ge 2 system by Arnold et al [5] resulted in spectroscopic constants for X 3 AE À g and 1 3 Å u , as well as for some low-lying singlet states. This, and another ZEKE study by Burton et al [6], confirmed 3 AE À g to be the ground state.…”
Section: Introductionmentioning
confidence: 97%